Beyond Precarity: Collective Practices and Political Subjectivities from Argentina’s Popular Economy - Álvarez, María Inés Fernández (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2018)
This article is based on an ongoing ethnographic research project with cooperatives of street vendors that are part of the Confederation of Workers of Popular Economy (CTEP), a recently formed union in Argentina whose objective is to represent workers of the “popular economy”. This research project aims to contribute to studies about the ways in which the so called “popular sectors” develop creative practices from their precarious positions to deal with the production and reproduction of life. In this work an analysis is done on the way in which this experience of precarity enabled a process of collective construction that connects a living past, anchored in subjective experiences, with a future that projects this experience in political terms in the form of a union. This article asserts that this process of collective construction creates tension between classical work divisions, such as formal/informal, salaried employee/non-salaried employee, worker movements/social movements, to the extent that wage earning work operates as a platform from which subjectivities are projected, less as material to be transformed and more as a foundation for generating collective rights.